SOCIO-PSYCHOLOGICAL ASPECTS OF A TEENAGER'S PERSONAL DEVELOPMENT IN THE EDUCATIONAL ENVIRONMENT OF PRE-EDUCATION - Aleksey V. Basov (Russian Journal of Education and Psychology)
Background. In the context of the development of informatization of society and the availability of diverse information on the Internet, adolescents have a great opportunity to expand beyond the educational institution. The formation of their social, cultural and psychological character is an important aspect for the future development of personality, since it is in adolescence that the foundations are laid for the correct definition of values, understanding of the "I" in this society. Therefore, in this context, it is important to involve adolescents in additional activities and creativity, which is possible within the framework of additional education.